Feelings of Blameworthiness and Their Associations With the Grieving Process in Suicide Mourning - Feigelman, William; Cerel, Julie (Frontiers in Psychology, 2020)
Abstract: Aims: This study focuses on identifying the correlates associated with the emergence of feelings of blameworthiness associated with a suicide or drug death and its consequences in complicating the grieving process. Method: Based on a mailed questionnaire survey of 575 bereaved parents, 462 who lost a child to suicide, 48 to a drug overdose, 37 to ordinary accidents, and 24 to natural causes, we compared and contrasted the patterns in the data with chi-square tests, correlations and multiple regression analyses. Results: Findings showed feelings of blameworthiness associated with grief difficulties, complicated grief, PTSD, depression and other mental health difficulties. Results also showed that being stigmatized by socially significant others, having a mixed or negative relationship with the deceased child prior to the death and a less happy marriage, among those presently married couples, all contributed to higher feelings of blameworthiness among the bereaved. Conclusions: Based on these findings, feelings of blameworthiness could serve as a good shorthand indicator of grief problems since it correlates so well with other grief difficulties and mental health problem measures. The importance of peer support is essential for avoiding the downward spiral associated with feelings of blameworthiness that can occur at any time during the grieving process.